Examining the Relationship between Carbon Emissions and Financial Performance: A Study in the BIST100 Index - Güneysu, Yusuf; Atasel, Oğuz Yusuf (Fırat University, 2022)
Since the industrial revolution, greenhouse gas emissions, especially carbon dioxide (CO2) emissions, cause climate change. In addition, the stakeholders of the firms are conscious about the management of climate change risks and demand non-financial information as well as financial information from the firms. Therefore, in the fight against climate change, firms provide explanatory information in sustainability and Carbon Disclosure Project (CDP) reports to their stakeholders about what they do to reduce greenhouse gas emissions and the number of emissions over the years. Because the amount of carbon emissions is not only for global warming, but also affects the financial performance of firms and jeopardizes their sustainability. In this context, the purpose of the study is to investigate the effect of carbon emissions on the financial performance of non-financial firms listed in the BIST100 Index in the period of 2014-2021 with panel regression models. Accordingly, the relationship between firms’ total carbon emissions and financial performance indicators (return on assets, return on equity, Tobin’s Q, net profit margin and earnings per share) has been tested. The findings show that although there is a significant and negative relationship between carbon emissions, return on assets and earnings per share, there is no significant relationship with other financial performance indicators.

Sanayi devriminden itibaren sera gazı emisyonları özellikle de karbondioksit (CO2) emisyonları iklim değişikliğine neden olmaktadır. Bununla birlikte firmaların paydaşları, iklim değişikliği risklerinin yönetimi konusunda bilinçlenmekte ve firmalardan finansal bilgilerinin yanı sıra finansal olmayan bilgiler de talep etmektedir. Dolayısıyla ikilim değişikliği ile mücadelede firmalar sera gazı emisyonlarını azaltmak için ne yaptıklarını ve yıllar itibariyle emisyon miktarının seyrini sürdürülebilirlik ve Karbon Saydamlık Projesi (Carbon Disclosure Project –CDP) raporlarında açıklayarak paydaşlarına bu konuda açıklayıcı bilgiler sunmaktadır. Zira firmaların karbon emisyon miktarları sadece küresel ısınma için değil aynı zamanda firmaların finansal performansını da etkilemekte ve sürdürülebilirliklerini tehlikeye atmaktadır. Bu çerçevede çalışmanın amacı, 2014-2021 döneminde BIST100 Endeksinde yer alan finans dışı firmaların finansal performansı üzerinde karbon emisyonlarının etkisini panel regresyon modelleri ile araştırmaktır. Bu doğrultuda firmaların toplam karbon emisyonları ile finansal performans göstergeleri (aktif kârlılığı, özsermaye kârlılığı, Tobin Q, net kâr marjı ve hisse başına getiri) arasındaki ilişki test edilmiştir. Bulgular, karbon emisyonları ile aktif kârlılığı ve hisse başına getiri arasında anlamlı ve negatif yönlü bir ilişki olmasına karşılık diğer finansal performans göstergeleri ile anlamlı bir ilişki olmadığını göstermektedir.
KARBON EMİSYONLARI İLE FİNANSAL PERFORMANS ARASINDAKİ İLİŞKİNİN İNCELENMESİ: BIST100 ENDEKSİNDE BİR ARAŞTIRMA